THE SUSTAINABILITY PRACTICES AND ITS EFFECT ON FINANCIAL LEAKAGES OF STAR CLASSIFIED HOTELS IN ETHIOPIA. - Behaile, Endalew Tegegne; Singh, Apar (Revista de turism - studii și cercetări în turism, 2021)
The purpose of this study was to test the effects of sustainability practice on financial leakage.It has also aimed at to investigate the effect of the reduction of financial leakage on competitive advantage of star classified hotels. A quantitative and cross-sectional approach was applied. Data were collected from all 242 star classified hotels using a survey questionnaire. CFA and SEM were applied to validate and to test the structural model respectively. The major findings were the higher sustainability practices of these star classified hotels could not more likely to reduced financial leakage of the studied star classified hotel in Ethiopia. Albeit, this research has brought a valuable insight on dimensions of financial leakage and the degree of sustainability practices and its implication for the reduction of financial leakage of star classified hotels in the country. Therefore, hotels in Ethiopia should give due attention for better sustainability practices implementation.